Comparison of the Effect of Hydrostatic and Dynamic High Pressure Processing on the Enzymatic Activity and Physicochemical Quality Attributes of ‘Ataulfo’ Mango Nectar - Manuel Alejandro Uranga-Soto; Manuel Alejandro Vargas-Ortiz; Josefina León-Félix; José Basilio Heredia; María Dolores Muy-Rangel; Dominique Chevalier-Lucia; Laetitia Picart-Palmade (Molecules, 2022)
The effects of hydrostatic (HHP) and dynamic (HPH) high-pressure treatments on the activity of pectin methylesterase (PME) and polyphenol oxidase (PPO) as well as the physicochemical quality attributes of ‘Ataulfo’ mango nectar were assessed. HHP reduced PME relative activity by 28% at 100 MPa for 5 min but increased PPO activity almost five-fold. Contrarily, HPH did not affect PME activity, but PPO was effectively reduced to 10% of residual activity at 300 MPa and at three passes. Color parameters (CIEL*a*b*), °hue, and chroma were differently affected by each type of high-pressure processing technology. The viscosity and fluid behavior were not affected by HHP, however, HPH changed the apparent viscosity at low dynamic pressure levels (100 MPa with one and three passes). The viscosity decreased at high shear rates in nectar samples, showing a shear-thinning effect. The results highlight how different effects can be achieved with each high-pressure technology; thus, selecting the most appropriate system for processing and preserving liquid foods like fruit beverages is recommended.